The effect of amorphous Si3N4 nanoparticles and magnetized distilled water on the mechanical properties and infrared transmittance of α-Al2O3 - Mahdi Darabi; Ehsan Mohammad Sharifi; Reza Vafaei; Akbar Eshaghi; Mohammad Reza Loghman-Estarki (Scientific Reports)
Abstract This study resolves the inherent trade-off between fracture toughness and mid-infrared transparency in α-Al2O3 ceramics. A novel shear-stress thin-layer process with magnetic-field-assisted dispersion achieves uniform distribution of 0.1 wt% amorphous Si3N4 nanoparticles and MgO/La2O3 sintering aids using 2 wt% DL dispersant at pH 10. Post-annealing at 1200 °C enhances fracture toughness by 126% (3.4 ± 0.2 to 7.68 ± 0.3 MPa m1/2) while reducing hardness from 23.6 ± 0.8 GPa to 12.6 ± 0.5 GPa, confirming improved ductility. XRD analysis verifies compressive residual stress (− 1.60 ± 0.08 GPa) and lattice strain (− 0.49 ± 0.05%). FESEM/EDS reveals grain refinement from 402 ± 18 nm to 124 ± 6 nm with homogeneity index exceeding 0.93. These microstructural modifications enable 85.3 ± 0.5% mid-infrared transmittance between 3 and 6 μm, surpassing conventional transparent alumina by 41%. This approach establishes a scalable method for designing multifunctional ceramics with simultaneous mechanical resilience and optical performance.